Pengaruh Customer Perceived Value dan Switching Barriers terhadap Customer Retention Produk Tabungan Batara iB - Mulya, Sri; Sari, Widya (Jurnal Dimamu, 2025)
Based on the results of observations, the background to this research is the tendency for fluctuations in Batara iB Savings customers at Bank BTN Syariah Bandung Branch Office. It is influenced by, among other things, the reduced perceived value of customers in saving due to minimal service and less than satisfactory transactional facilities. Lack of switching barriers (Switching Barriers) by banks resulting in a decline, customers moving payroll, many offers from other banks and customer environmental factors that require switching. This research aims to determine the influence of Customer Perceived Value and Switching Barriers on Customer Retention of Batara iB Savings Products at Bank BTN Syariah Bandung Branch Office, both partially and simultaneously.The object of the research is Batara iB Savings customers at Bank BTN Syariah Bandung Branch Office. The type of research is associative quantitative with primary data types and uses data collection techniques in the form of observation, interviews, literature studies and questionnaires. Meanwhile, the sampling technique is non-probability sampling with a purposive sampling type. The population is all Batara iB Savings customers at Bank BTN Syariah Bandung Branch Office, totaling 1,019 people with a sample of 92 people. The results of the research show that Customer Perceived Value and Swithching Barriers partially influence Customer Retention by 60,3% and 43,6%, while simultaneously the influence is 68,6%.